SO2 Observations and Sources in the Western Pacific Tropical Tropopause Region. Issue 23 (4th December 2018) - Rollins, Andrew W.; Thornberry, Troy D.; Atlas, Elliot; Navarro, Maria; Schauffler, Sue; Moore, Fred; Elkins, James W.; Ray, Eric; Rosenlof, Karen; Aquila, Valentina; Gao, Ru‐Shan
Abstract: Sulfur dioxide (SO2 ) is one of the primary source gases for aerosols in the atmosphere. Even at low concentrations, its presence in the upper troposphere and lower stratosphere (UT/LS) provides an important source for aerosol nucleation and growth, and SO2 has been postulated to be important for the stratospheric sulfur budget. To understand aerosol nucleation and global radiative effects, it is therefore important to quantify how much SO2 emitted from biogenic and anthropogenic processes at the surface is transported into the UT/LS. Much of the potential transport is expected to occur in regions of significant deep convection such as the western Pacific warm pool. Here we use measurements from the National Aeronautics and Space Administration (NASA) WB‐57F Pacific Oxidants Sulfur Ice and DehydratiON (POSIDON) mission that was based in Guam in 2016 to examine the distribution and sources of SO2 in the western Pacific UT/LS region. During POSIDON, a few events related to volcanic emissions as well as transport by tropical cyclones were observed that brought up to 86 pptv of SO2 above 14‐km altitude. Overall however, the measurements corroborate our earlier findings that SO2 near the tropical tropopause is typically quite low ( 5 pptv) and globally the transport of SO2 into the stratosphere is likely a minor source of stratospheric aerosols. Key Points: We report new in situ observations of UT/LS SO2 above the western Pacific Volcanic and anthropogenic SO2 in the UT/LS are identified Low ozone above the western Pacific does not appear to be an important factor allowing SO2 transport into the UT/LS